32‐1: Oxide Semiconductor Field‐Effect Transistor for High‐Resolution Displays Capable of Deep Black Display. Issue 1 (28th June 2022) - Okazaki, Yutaka; Sawai, Hiromi; Endo, Masami; Motoyoshi, Ryousuke; Shimada, Daigo; Kunitake, Hitoshi; Yamazaki, Shunpei; Huang, Kou-Chang; Yoshida, Hiroshi; Chen, Min-Cheng; Liao, Ming-Han; Chang, Shou-Zen
Abstract : In this paper, a small‐sized oxide semiconductor field‐effect transistor (OSFET) is developed as a driving transistor suited for small high‐resolution displays of virtual reality/augmented reality devices. We examine the electrical characteristics of an OSFET with a channel length of 200 nm to note its excellent saturation characteristics, high breakdown voltage, high reliability, and low off‐state current. Additionally, we fabricate a 3207‐ppi organic light‐emitting diode display to examine the performance of the OSFET in an active panel. The experimental results showed a high contrast ratio.